2014
DOI: 10.1024/2235-0977/a000078
|View full text |Cite
|
Sign up to set email alerts
|

Spezifische Effekte von EEG-basiertem Neurofeedbacktraining auf kognitive Leistungen nach einem Schlaganfall

Abstract: Der Schlaganfall ist weltweit die häufigste neurologische Erkrankung und oft treten Störungen kognitiver Funktionen als Folgeerscheinungen auf. In dieser Studie wurde untersucht, inwiefern ein Elektroenzephalographie (EEG) basiertes Neurofeedbacktraining (NFT) genutzt werden kann, um neuronale Plastizität nach einem Schlaganfall anzuregen und spezifische kognitive Leistungen von Schlaganfallpatienten zu verbessern. Vorgängerstudien an neurologisch gesunden Probanden konnten zeigen, dass eine willentliche Erhöh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 43 publications
4
12
0
Order By: Relevance
“…More precisely they showed performance improvements in cognitive domains of information processing speed, attention and concentration as well as in executive functions. This result supports prior findings in stroke patients who also showed cognitive improvements due to SMR based NF training, which was performed in a standard lab environment [5][6][7]. Furthermore, this is the fust study showing beneficial effects of NF training on cognitive functions in patients with MS.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…More precisely they showed performance improvements in cognitive domains of information processing speed, attention and concentration as well as in executive functions. This result supports prior findings in stroke patients who also showed cognitive improvements due to SMR based NF training, which was performed in a standard lab environment [5][6][7]. Furthermore, this is the fust study showing beneficial effects of NF training on cognitive functions in patients with MS.…”
Section: Discussionsupporting
confidence: 92%
“…It is assumed that during SMR based NF training, the effects of both SMR and beta power changes are related to improvements in cognitive functions [26]. The present NF training results are comparable to the results of prior NF training studies in which the NF training was perfonned by an EEG expert in a laboratory using standard EEG equipment [5][6][7]. In these prior studies, participants were also able to linearly increase SMR power, while other frequencies were more or less independent.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…However, the generalizability of these prior findings is limited due to the incomplete description of training-specific EEG signal changes as well as the absence of control groups. A study by Hofer et al (2014) is one of the first NF training studies investigating the effects of SMR and Theta/Beta quotient (4-8/13-21 Hz, T/B NF training) based NF training on cognitive functions in stroke patients and healthy controls [ 33 ]. The authors could demonstrate that stroke patients with memory impairments showed specific performance improvements in declarative memory tasks after SMR NF training, while stroke patients with deficits in attention and inhibition showed specific improvements in inhibitory control and cognitive flexibility after repeated T/B NF training.…”
Section: Introductionmentioning
confidence: 99%